FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI KEBERLANGSUNGAN USAHA KERAJINAN BATOK KELAPA DI KELURAHAN PURBALINGGA WETAN KECAMATAN PURBALINGGA KABUPATEN PURBALINGGA - Muhamad Misbah Azzamani; Dumasari Dumasari; Pujiati Utami (Universitas Muhammadiyah Purwokerto, 2016)
The activity of farming does not only refer to how much the are of land or how many farmers produce the meal product from plants or animals raised. Farm business has been done from head water namely from pre production to down stream namely the process of post harvest. There are some farming business done by the people of Purbalingga, one of the potential business to develop human resources is Coconut farming is well as its waste business. The business of coconut in Purbalingga Wetan village is one of examples of the down stream farming activity. The products of the coconut shell are irus, ciri, mutu, soled, rice scoup (centong), and other handicraft. The social factors influencing thecontinuity of cococnut shell handicraft were: the ability of the farmers and crafstmen in providing the material, the networking, goverment’s and family’s supports, skill in heritance from previous generation, the ability to give confidence, and the farmer’s skill to recycle the waste of coconut shell to be handicraft. The economy factors affecting the continuity were: the price determination of the product, the craftsmen’s skill to gain the main revenue, marketing channel used either director indirect system, and the product demand of handicraft the always improving.